PERAN GENDER DALAM PENGAMBILAN KEPUTUSAN AUDIT - SETIAWAN, YUPIE (Universitas Katolik Widya Mandala Surabaya, 2012)
Some research in the field of audit findings that getting there is a difference based decision-making factor of gender audit. Auditors with the female sextend to have higher sensitivity than the auditor of men, especially in terms of ethical behavior, and differences in the sensitivity of the causes of differences in decision making. In addition, there are findings which concluded that an auditor's decision can not be based on the gender factor. It means that there is no difference between the auditor's decision-making with male gender and auditor with the female sex. Results of analysis showed that the presence or absence of differences indecision-making based on the gender factor can not be universally applicable. Although both auditor with the female sex or male sensitivity to the level of ethical behavior can be different and this causes the auditor ethical behavior of women is higher than the auditor with male gender can not be generalized.